Design of a wideband transition between coaxial probe and parallel-plate waveguide - Shen, Junfei. (2013)
This final year project contains two designs. The first one is the design of a wideband transition between coaxial probe and parallel-plate waveguide. The second is the design of coaxial to water-layer transition. Both designs have been structured and simulated using High Frequency Structural Simulator. The wideband coaxial-to-radial transition has been fabricated to verify the design concept. Simulated and tested results are presented and discussed in the report.